Menstrual Cup Use and Intrauterine Device Expulsion in a Copper Intrauterine Device Contraceptive Efficacy Trial [OP01-1B]. (May 2020) - Long, Jill; Schreiber, Courtney; Creinin, Mitchell D.; Kaneshiro, Bliss; Nanda, Kavita; Blithe, Diana
Abstract : INTRODUCTION: Menstrual cup use for menstrual hygiene is increasingly popular. We evaluated relationship of menstrual cup use and intrauterine device (IUD) expulsion in a prospective trial of two copper IUDs. METHODS: An ongoing 3-year contraceptive efficacy trial randomized women to one of two copper IUDs, with successful placement in 1, 092 women. Institutional Review Board approval was obtained, and all subjects provided informed consent. Follow-up visits in the first year occurred at 6 weeks, and then 3, 6, and 12 months after insertion. At nine months after initiating enrollment, we modified the protocol to advise subjects against concurrent menstrual cup use with the IUD. We evaluated the association of menstrual cup use and expulsion risk over the first 24 months of study conduct. RESULTS: Overall, 266 (24.4%) women reported menstrual cup use. At 24 months after initiating enrollment, 46 (17.3%) cup users and 43 (5.2%) non-users experienced expulsion (odds ratio 3.81 [95% CI 2.45-5.92]). Fourteen (30.4%) menstrual cup users with expulsion reported the event occurred during menstrual cup removal. At Year 1 of the study, expulsion rates among menstrual cup users and non-users were 14.3% and 4.7%, respectively (P<.001). By the end of Year 2, these rates were 23.2% and 6.5% (P<.001). CONCLUSION: We found higher than expected IUD expulsion rates in menstrual cup users amongst participants in a prospective trial of two copper IUDs. Copper IUD users should be cautioned that concurrent menstrual cup use increases the risk of IUD expulsion and expulsion risk continues with ongoing menstrual cup use.